Efficiency of local service provision in Zambia's health, education and road sectors: implications for decentralisation and the effectiveness of budget support - Stefan Leiderer; Maximilian Geigenmüller; Anja Hornig; Kathrin Kästle; Christopher Smith; Franziska Tröger Tröger (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
This study was produced in close cooperation with the Economic Association of Zambia (EAZ) within the framework of DIE's postgraduate training programme. It is based on field-work conducted in Zambia between February and April 2010 and forms part of the background work conducted for an international joint evaluation of Budget Support in Zambia. The main aim of this study is to provide a clearer understanding of how budget allocations in Zambia are transformed into service delivery and the provision of public goods in selected sectors (health, education, roads), and how the operational efficiency of budget implementation in Zambia could be improved. The study finds that weaknesses in operational efficiency at local government level are due to two main systemic determinants, namely a systemic lack of resources for core PFM activities and the concentration of control over resources and decision-making at central government level. The findings imply that there is little potential for short term efficiency gains in service delivery and that only systemic PFM reforms can lead to increased operational efficiency. The study draws conclusions on the implications for Zambia's decentralisation policy and the use of budget support as an aid modality.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen